Ji?nekoloji?k onkoloji?de şi?löz asi?t ve yöneti?mi? - Çelik, Hüsnü; Gürateş, Bilgin; Kavak, Burçin; Aygün, Banu; Aygen, Erhan; Aygün, Cem (My University, 2009)
Chylous ascites (CA) content of thoracic or intestinal lymph in the abdominal cavity with the resulting content is rich in triglycerides or lean-looking milky is defined as peritoneal fluid accumulation. Real chylous effusions, appearance, depending on the cellular degeneration and significantly lower triglyceride containing the chyliform or pseudochylous effusion should be separated. As the underlying basis of CA treatment are detected and treated depends on the cause. Nutritional support in the treatment of patients with medical and surgical options are used.
Keywords: Chylous ascites; Gynecologic oncology; Retroperitoneal lymphadenectomy